Evolution of Clinical Skills Assessment in the USMLE: Looking to the Future After Step 2 CS Discontinuation. (September 2021) - Katsufrakis, Peter J.; Chaudhry, Humayun J.
Abstract : The COVID-19 pandemic interrupted administration of the United States Medical Licensing Examination (USMLE) Step 2 Clinical Skills (CS) exam in March 2020 due to public health concerns. As the scope and magnitude of the pandemic became clearer, the initial plans by the USMLE program's sponsoring organizations (NBME and Federation of State Medical Boards) to resume Step 2 CS in the short-term shifted to long-range plans to relaunch an exam that could harness technology and reduce infection risk. Insights about ongoing changes in undergraduate and graduate medical education and practice environments, coupled with challenges in delivering a transformed examination during a pandemic, led to the January 2021 decision to permanently discontinue Step 2 CS. Despite this, the USMLE program considers assessment of clinical skills to be critically important. The authors believe this decision will facilitate important advances in assessing clinical skills. Factors contributing to the decision included concerns about achieving desired goals within desired time frames; a review of enhancements to clinical skills training and assessment that have occurred since the launch of Step 2 CS in 2004; an opportunity to address safety and health concerns, including those related to examinee stress and wellness during a pandemic; a review of advances in the education, training, practice, and delivery of medicine; and a commitment to pursuing innovative assessments of clinical skills. USMLE program staff continue to seek input from varied stakeholders to shape and prioritize technological and methodological enhancements to guide development of clinical skills assessment. The USMLE program's continued exploration of constructs and methods by which communication skills, clinical reasoning, and physical examination may be better assessed within the remaining components of the exam provides opportunities for examinees, educators, regulators, the public, and other stakeholders to provide input.